Titanosilicate Epoxidation Catalysts: A Review of Challenges and Opportunities - Smeets, Valentin; Gaigneaux, Eric M.; Debecker, Damien P. (ChemCatChem, 2022)
Epoxidation reactions are tremendously important for modern chemistry, as they lead to series of highly useful bulk and fine chemicals, monomers, and intermediates for organic synthesis. Progress in epoxidation processes goes hand in hand with the advancement made in catalysis science. In this context, heterogeneous catalysts, and particularly Ti‐based formulations, are playing a central role and have seen tremendous developments over the past two decades, leveraging on advanced materials science. The aim of this review is to illustrate the various strategies of titanosilicate catalysts preparation that can lead to more versatile, more performant, and greener epoxidation processes. We successively cover (i) supported catalysts, obtained by the grafting of Ti species onto preformed silica supports, (ii) microporous crystalline titanosilicates (zeolites), and (iii) amorphous titanosilicates obtained by sol‐gel chemistry. For each category, with an emphasis on catalyst preparation, the challenges that have to be tackled to boost catalyst performance are highlighted. From that point, we present a critical review of the different approaches that have been proposed in the primary literature to tailor the properties that govern catalysts performance (activity, selectivity, stability, ease of handling). This is done by better controlling the nature of the active surface species, adapting particles size and shape, optimizing texture, modifying surface chemistry, etc. These lines of attack encompass molecular approaches for the grafting of well‐defined species, top‐down and bottom‐up synthesis of hierarchically porous zeolites, advanced sol‐gel routes potentially performed in non‐conventional media or coupled with original processing, preparation of self‐standing monoliths, etc. Future research directions are discussed with emphasis on the application scope of new catalytic materials and possible approaches to increase catalyst performance. Mesoporous catalysts: This review presents an overview of the recent advances in the development of titanosilicate catalysts used in epoxidation and critically addresses the key relation between the preparation method and the physico‐chemical properties that govern catalytic performance.